EVALUASI PROGRAM PENGEMBANGAN USAHA AGRIBISNIS PERDESAAN DI KECAMATAN KALAWAT KABUPATEN MINAHASA UTARA - Gabriela H. Kaawoan; Celcius Talumingan; Tommy F. Lolowang; Lyndon R.J. Pangemanan (COCOS, 2014)
ABSTRACTGabriela Hana Kaawoan. Evaluation Of Agribusines Development Program in Kalawat District North Minahasa Regency. Under Guidiance Celcius Talumingan as Chairman, Tommy Lolowang and Lyndon Pangemanan as members.The objective of this research is to evaluate. PUAP Program in Kalawat sub district Minahasa regency based on the contex, input, procces, product. That was used in this research is purposive sampling method. Data used in this research was primary and secondary data. Primary data were collected by interviewing members and farmes group and GAPOKTAN management in 5 villages that accept PUAP program in Kalawat sub district and secondary data were collected from institutions that related with this research. Analysis in this research was descriptive with CIPP method, tabulation and scoring analysis. Revenue and cost of farmer was used to cost farmer’s incomeThe research result showed that for PUAP program based on the context, agent of extension and institutions that related with the research obtained high interpretation with index 100%. It can be proved from agriculture industries that improve, good response from farmes to this program the readiness of extension agent to improve agribusines industry in village through socialization and farmers group activity, agent of extension couwel PUAP programe farmers roufinely, and government strategy to make PUAP program success, based an input aspect of PUAP program to evaluation to farmer, investigation and related institution get high on average, but there was a statement that get low interpretation with index 67,2% that was farmes altitude awy, less capital in starting their business, capital the was used was their our capital and the business hasn’t improved yet. Seen from process aspect that PUAP programe evaluation in farmers investigator and institution that related get high average. However there was a low interpretation with 67,2% index that was the attitude of farmer before this PUAP program.This attitude was the farmer was less motivated, less capital in running the business so that the business was less developed. From the process aspect, evaluation of PUAP program to farmer, agent of extension and institution obtained high result on average. However, the obstacle was the return of loan capital was not running well. From the product aspect, the PUAP evaluation on farmer, agent of extension and institution obtansl high result with 100 index. This can be seen raised from farmers income increase that they before Rp 1.637.551/Ha and after PUAP the income rate raised become Rp 3.357.524/Ha von average farmers start new business land raise, and production improves, due to GAPOKTAN went well cording rules and could improve well through. GAPOKTAN manager over all PUAP evaluation program to farmers through CIPP evaluation got 87.6%, to agent of extension through CIPP evaluation 99,1% and to related instituation got 97,1%.5Even the overall the interpretation was high, but in return of capital had not gone well, acompanion of agent of extens maximum to farmers and observation of agriculture department directly had not done routinely.